Markiisitar: Kertomus - Sand, George, 1804-1876; Tuura, Timo, 1885-1963 (Salt Lake City, UT : Project Gutenberg, 2016)
"Markiisitar: Kertomus" by George Sand is a novel written in the late 19th century. The book centers around the character of Markiisitar de R----, an elderly noblewoman reflecting on her life and relationships, particularly concerning her past loves and the societal norms surrounding marriage and womanhood during her time. Through her recollections, themes of love, social status, and personal introspection emerge. At the start of the novel, we are introduced to the Markiisitar, who is portrayed as not particularly intelligent despite her noble status. She expresses a cynical view on her relationships, including the loss of her longtime companion, the Count de Larrieux. As she begins to recount her life story and experiences in society, she reveals memories that highlight her lack of awareness about emotional connections and self-deception. The opening establishes a tone where the Markiisitar seeks to gain empathy and understanding for her past decisions, suggesting an exploration of the complexities of love and the constraints of social expectations. (This is an automatically generated summary.)
Release date is 2016-12-03
Produced by Tapio Riikonen
Keywords: France -- Fiction; Women -- France -- Fiction